2019
DOI: 10.1186/s12906-019-2623-4
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of hydro-alcoholic extract of Achillea wilhelmsii C. Koch on indomethacin-induced gastric ulcer in rats: a proteomic and metabolomic approach

Abstract: Background: Gastric ulcer is one of the most prevalent diseases worldwide. In Iranian folk medicine, Achillea wilhelmsii (AW) is used as a treatment for gastric ulcer. Previous reports also mentioned Antiulcerogenic properties for this herbal plant. This study investigated the therapeutic effects of Achillea wilhelmsii C. Koch extract on indomethacin-induced gastric lesion in rats, from both proteomic and metabolomic perspectives. Methods: The rats were divided into 4 groups. Gastric ulceration was induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…A. wilhelmsii K.Koch, a synonym of accepted name A. santolinoides subsp. wilhelmsii (K.Koch) Greuter [ 15 ], has been shown to have antihyperlipidemic, antihypertensive, and antimycobacterial properties [ 16 ], and has potential for the treatment of indomethacin-induced gastric ulcers [ 17 ]. The treatment with A. wilhelmsii hydroalcoholic extract significantly reduced triglycerides, total cholesterol, and low-density lipoproteins, and reduced diastolic and systolic blood pressure [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A. wilhelmsii K.Koch, a synonym of accepted name A. santolinoides subsp. wilhelmsii (K.Koch) Greuter [ 15 ], has been shown to have antihyperlipidemic, antihypertensive, and antimycobacterial properties [ 16 ], and has potential for the treatment of indomethacin-induced gastric ulcers [ 17 ]. The treatment with A. wilhelmsii hydroalcoholic extract significantly reduced triglycerides, total cholesterol, and low-density lipoproteins, and reduced diastolic and systolic blood pressure [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through the enrichment analysis of the KEGG pathway, it was found that some pathways with common target enrichment, such as the PI3Kā€AKT signaling pathway, MAPK signaling pathway, and HIFā€1 signaling pathway, can also regulate gastric mucosal angiogenesis through VEGF [41]. In addition, the occurrence of GU can lead to the decrease of ALB and the increase of other proteins, while serum albumin is used as a predictor of upper gastrointestinal bleeding [42], which also plays a role in the occurrence and development of GU to a certain extent [32].…”
Section: Discussionmentioning
confidence: 99%
“…In Iranian folk medicine, Achillea wilhelmsii (Asteraceae) is used to treat gastric ulcers. Koushki et al [12] suggested that the extract of A. wilhelmsii could heal indomethacin-induced gastric ulcers. However, the authors evaluated the gastroprotective activity of A. wilhelmsii without using any canonical model to verify its effect on gastric healing.…”
Section: Gastroprotective Plants That Modulate Oxidative and Inflammatory Parametersmentioning
confidence: 99%